Diversity and distribution patterns of antennal sensilla in Hydropsychidae (Insecta, Trichoptera) - Abu Diiak, Kseniia; Valuyskiy, Mikhail; Melnitsky, Stanislav; Ivanov, Vladimir (Biological Communications, 2021)
Structure and distribution of antennal sensilla were studied in males of 19 species of the caddisfly family Hydropsychidae by using scanning electron microscopy (SEM). Eleven types of sensilla were found: long trichoid, chaetoid, thick chaetoid, curved trichoid, coronary, basiconic, styloconic and four types of pseudoplacoid sensilla (mushroom-like, auricillic, ribbed, and T-shaped). Thick chaetoid, ribbed pseudoplacoid, and T-shaped pseudoplacoid sensilla were found only in Macronematinae. The great diversity of pseudoplacoid sensilla originated from a mushroom-like type, which also has a variable structure. Basal flagellomeres in the majority of studied species are equipped with ventrally positioned sensory fields of curved trichoid sensilla. In contrast to Arctopsychinae and Hydropsychinae, the increased number of these sensilla in the fields was noted for Diplectroninae and Smicrideinae. Most Macronematinae show a reduction of sensory fields and a strongly decreased average number of curved trichoid sensilla on distal segments. The great differences found in the studied family probably indicate a rapid function-related evolution of the antennal sensory surface structures in the caddisfly family Hydropsychidae.